THE SELECTION OF A BEE POLLINATING CUCUMBER HYBRIDS OF GHERKIN TYPE - T. I. Mokryanskaya (Овощи России, 2019)
Research work  was  carried  out  at  the  Pridnestrovian research  Institute of agriculture in 2014-2017 in film greenhouses (spring-summer  and summer turnover) and in the open ground when grown in the spreading and on the trellis. Much attention was paid to the degree and nature of the manifestation of heterosis in F1   hybrids, which were estimated by early and total yield, yield of standard fruits, yield of gherkins. The standards were F1      hybrids: Zubrenok and Ajax. The purpose of the work is the selection of bee-pollinated hybrids of universal cucumber for protected and open ground. Created in  the  Transnistrian  agricultural research Institute pollinated by bees hybrids of cucumber universal destination F1   Korolek, F1   Sverchok, F1   Viurok is characterized by a high yield of gherkins in both factions that is currently the most promising in the areas of plant breeding and seed production of hybrids and commercial production of cucumber.  New  bee-pollinated hybrids: F1   Korolek, F1 Sverchok, F1 Viurok pass state variety testing in the Republic of Moldova and entered in the Register of breeding achievements in Transdniestria in 2017.